The zinc-finger transcription factor Blimp1/Prdm1 is required for uterine remodelling and repair in the mouse - Maria-Eleni Xypolita; Mubeen Goolam; Elizabeth K. Bikoff; Elizabeth J. Robertson; Arne W. Mould (Nature Communications)
Abstract The zinc finger transcription factor Blimp1/PRDM1 regulates gene expression in diverse cell types. Its activity controls the maternal decidual response at early post-implantation stages of development. The present experiments demonstrate surprisingly that Blimp1 activity in the uterus is required for tissue remodelling at sites of embryonic failure. Moreover Blimp1 mutant females are refractory to RU486 induced decidual shedding. RNA-seq together with immunostaining experiments strongly suggest that the failure to up-regulate expression of the matrix metalloprotease Mmp10 in combination with insufficient suppression of BMP signalling, likely explain Blimp1-dependent phenotypic changes. In the post-partum uterus Blimp1 together with Mmp10 are highly upregulated at sites of tissue repair following placental detachment. Conditional Blimp1 removal significantly impairs the re-epithelization process and severely impacts involution of the endometrium and luminal epithelium. Overall these results identify Blimp1 as a master regulator of uterine tissue remodelling and repair.